2015
DOI: 10.3109/00365521.2015.1079645
|View full text |Cite
|
Sign up to set email alerts
|

The celiac iceberg: from the clinical spectrum to serology and histopathology in children and adolescents with type 1 diabetes mellitus and Down syndrome

Abstract: Objective: The objective of this study is to investigate the occurrence of gastrointestinal (GI) and extraintestinal symptoms in children and adolescents with type 1 diabetes mellitus (DM1) and Down syndrome (DS) and their association with specific antibodies and histopathology of celiac disease (CelD), representing its clinical forms in the iceberg. Material and methods: Cross-sectional study (November 2009–December 2012) conducted at an outpatient care facility in Northeast Brazil including patients [DM1 (n … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 36 publications
1
13
1
2
Order By: Relevance
“…Studies from different Brazilian regions have shown a wide frequency range of GI manifestations in patients with T1DM and CD (38.3%‐80.0%) . In the present study, almost two‐thirds of patients (71.4%) with biopsy‐proven CD reported unspecific GI symptoms, predominantly abdominal pain and distension.…”
Section: Discussionsupporting
confidence: 45%
See 2 more Smart Citations
“…Studies from different Brazilian regions have shown a wide frequency range of GI manifestations in patients with T1DM and CD (38.3%‐80.0%) . In the present study, almost two‐thirds of patients (71.4%) with biopsy‐proven CD reported unspecific GI symptoms, predominantly abdominal pain and distension.…”
Section: Discussionsupporting
confidence: 45%
“…In our study, which is the largest cohort in Brazil to date, the prevalence was 5.6%. This frequency is higher than that observed in most studies carried out in different regions of Brazil (Table ) . The only Brazilian study showing a higher prevalence (15.8%) of biopsy‐proven CD was based in a very small sample (19 patients with T1DM) .…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…Compared to the general population, literature has provided evidence that CD is more frequent in patients with some genetic and autoimmunological diseases, these diseases include type 1 diabetes [ 5 , 6 ], autoimmune thyroid disease [ 7 , 8 ], autoimmune hepatitis [ 9 ] and Down syndrome (DS) [ 10 ]. Although the prevalence of CD in those diseases varied substantially among studies, a systematic review with meta-analysis showed that 6 % of patients with type 1 diabetes have biopsy-confirmed celiac disease [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…The pooled prevalence of coeliac disease among first degree relatives is 7.5% 19 . Recent studies show that children with diabetes mellitus type 1 and Down syndrome have a high prevalence of coeliac disease, which may present with abdominal pain and constipation rather than classical diarrhoea 20 — also pointing to case finding in this group. Although current evidence is not sufficient to support mass screening for coeliac disease, active case finding is appropriate in high risk groups 12 …”
Section: Clinical Presentationmentioning
confidence: 99%